Finding yourself in your wardrobe: An exploratory study of lived experiences with a capsule wardrobe. (January 2022) - Bardey, Aurore; Booth, Madison; Heger, Giuliana; Larsson, Jonas
Fashion overconsumerism and overproduction have placed the fashion industry one of the world's most polluting industries. In addition to its environmental impact, research has shown that materialism leads to lower life satisfaction and decision fatigue. Recently, studies have highlighted an increased interest in sustainable fashion consumption and ethical lifestyle. The capsule wardrobe phenomenon, that is, defined by limited clothing pieces that focus on quality, longevity, and minimal or classic design, has gained exposure as a road map for consumers to remain fashionable while consuming less. Until today, no research has evaluated the impact of minimalist wardrobe on consumers. Using a phenomenological approach, the present study method to understand 10 female participants' lived experiences with a capsule wardrobe. Our results showed a positive impact of a 3-week capsule wardrobe on our participants who felt less stressed, detached from fashion trends, have found joy in their fashion style, and enhanced their awareness of conscious consumption. Our findings highlight the richness of minimalism, sustainable consumption, and self-expression through an innovative and relevant phenomenon.